Effect of fermentation using different lactic acid bacteria strains on the nutrient components and mineral bioavailability of soybean yogurt alternative - Gan, Jing; Kong, Xiao; Wang, Kuaitian; Chen, Yuhang; Du, Mengdi; Xu, Bo; Xu, Jingru; Wang, Zhenhua; Cheng, Yongqiang; Yu, Tianying (Frontiers in Nutrition, 2023)
Introduction Analysis of the composition of yogurt alternatives (YAs) during fermentation provides critical information for evaluating its quality and nutritional attributes. Method We investigated the effects of homotypic (HO) and heterotypic (HE) lactic acid bacteria on the nutritional and mineral bioavailabilities of soybean YA (SYA) during fermentation. Result The acidic amino acid (Glu, Asp) and organic acid contents in HO-fermented YA were increased from 2.93, 1.71, and 7.43 mg/100 g to 3.23, 1.82, and 73.47 mg/100 g, respectively. Moreover, both HO and HE lactic acid bacteria fermentation enhanced mineral absorptivity. They altered the molecular speciation of minerals from a large molecular type (2,866 Da) to a small molecular type (1,500 Da), which was manifested in a time-dependent manner. Furthermore, YA substantially increased the bone mass in a zebrafish osteoporosis model, further highlighting the potential of lactic acid bacterial fermentation for mineral bioavailability. Discussion This study provides a foundation for understanding the effects of fermentation conditions on the composition and bioavailability of minerals in YA and can assist in its production.